Synthesis, In Vitro and In Silico Molecular Docking Studies of Novel Phthalimide–Pyrimidine Hybrid Analogues to Thalidomide as Potent Antitubercular Agents - Shehta, Wael; Alsaiari, Norah A.; Farag, Basant; Abdel-Aziz, Marwa M.; Youssif, Shaker; Elfeky, Sherin M; El-Kalyoubi, Samar; Osman, Nermine A. (SynOpen, 2025)
Condensation reaction of aromatic aldehydes with 2-(6-amino-2-chloropyrimidin-4-yl)isoindoline-1,3-dione and 2-(6-amino-2-hydrazineylpyrimidin-4-yl)isoindoline-1,3-dione afforded 2-(2-chloro-6-((3 alkylbenzylidene)amino) pyrimidin-4-yl)isoindoline-1,3-dione derivatives 6a–f and 2-(6-amino-2-(2-(arylidene)hydrazinyl)pyrimidin-4-yl)isoindoline-1,3-dione derivatives 8a–f, respectively, as phthalimide–aminopyrimidine hybrids. The compounds showed a wide range of antitubercular activities against sensitive MDR and XDR M. tuberculosis strains, with 8f and 6a showing the highest activity; these compounds inhibited sensitive M. tuberculosis with MIC of 0.48 and 0.98 μg/mL, respectively, comparable to isonizide (INH) (MIC = 0.12 μg/mL). Both 8f and 6a inhibited the MDR strain with MIC of 1.95 and 7.81 μg/mL, respectively, and XRD with MIC of 7.81 and 15.63 μg/mL, respectively. Both 8f and 6a inhibited mycobacterial InhA enzyme in vitro (IC50 = 0.717± 0.033 μM and 1.646± 0.069 μM, respectively). Molecular docking simulations revealed that 8f and 6a were also capable of interacting at the catalytic site of the InhA enzyme via binding with NAD+ and Tyr158, in a manner similar to that of the native ligand. Compounds 6a and 8f exhibited physicochemical properties of oral bioavailable drug-like compounds with high gastrointestinal absorption. Predictions showed that the compounds are unlikely to have side effects on the CNS and no anticipated hepatotoxicity, mutagenicity, or acute oral toxicity was identified in models.
Keywords: Mycobacterium tuberculosis; ADMET studies; docking simulation; enzyme inhibition; phthalimide–pyrimidine hybrids